Conversion of the primary aneurysmal bone cyst into osteogenic sarcoma following treatment with percutaneous sclerotherapy using polidocanol injection - Kishor, Kamal; Ragase, Ashish; Kapoor, Love; Kumar, Venkateshan S.; Mirdha, Asit R.; Khan, Shah A. (International Journal of Research in Orthopaedics, 2024)
The intralesional injection of sclerosing agents has been identified as a safe method for treating primary aneurysmal bone cysts (ABC). However, to the best of our knowledge, there have been no reported instances in the literature of a primary ABC transforming into osteogenic sarcoma following complete healing facilitated by an intralesional sclerosing agent, such as polidocanol. We present the case of a 20-year-old female diagnosed with a histologically proven primary ABC located at the distal end of the tibia. She underwent a series of 5 intralesional injections of 3% polidocanol (hydroxypolyaethoxydodecan) and achieved complete clinical and radiological healing. However, after 10 years, her symptoms resurfaced, and subsequent histological examinations revealed osteogenic sarcoma. Surgical excision was performed, followed by bone grafting and ankle arthrodesis. This case suggests that intralesional alcohol injections might not prevent the inherent potential for malignant transformation of primary ABCs. To ascertain whether such injections increase the risk of sarcomatous conversion, further long-term follow-up studies are imperative.